2014
DOI: 10.1370/afm.1666
|View full text |Cite
|
Sign up to set email alerts
|

The Family Physician's Perceived Role in Preventing and Guiding Hospital Admissions at the End of Life: A Focus Group Study

Abstract: PURPOSE Family physicians play a pivotal role in providing end-of-life care and in enabling terminally ill patients to die in familiar surroundings. The purpose of this study was to explore the family physicians' perceptions of their role and the difficulties they have in preventing and guiding hospital admissions at the end of life.METHODS Five focus groups were held with family physicians (N= 39) in Belgium. Discussions were transcribed verbatim and analyzed using a constant comparative approach.RESULTS Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
(44 reference statements)
0
29
1
1
Order By: Relevance
“…Despite a similar percentage of people who were hospitalised at least once in all four countries, the percentage of people readmitted to hospital in the Netherlands was only half as high as that in the other countries. It has been suggested that GPs’ role as gatekeepers to secondary and tertiary care in the Netherlands, may reduce hospitalisations and hospital deaths 36. However, our cross-national comparison shows that this alone is not a sufficient explanation.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Despite a similar percentage of people who were hospitalised at least once in all four countries, the percentage of people readmitted to hospital in the Netherlands was only half as high as that in the other countries. It has been suggested that GPs’ role as gatekeepers to secondary and tertiary care in the Netherlands, may reduce hospitalisations and hospital deaths 36. However, our cross-national comparison shows that this alone is not a sufficient explanation.…”
Section: Discussioncontrasting
confidence: 64%
“…It is thus perhaps gatekeeping by GPs who are trained and supported in preventing inappropriate hospitalisations at the end of life, combined with a high level of coordination in primary care,21 that helps reduce hospitalisations and hospital deaths rather than the gatekeeping system alone. This hypothesis is supported by evidence from qualitative research that suggests that GPs’ competence and attitude regarding end-of-life care and support by local specialist palliative care services are important in avoiding hospitalisations at the end of life 36. It might thus be a combination of structural factors of the healthcare system (eg, gatekeeping role, coordination of primary care) and care provision factors (eg, specialist support) that either drives or curbs these hospitalisations.…”
Section: Discussionmentioning
confidence: 92%
“…[6][7][8][9] GPs, along with the wider palliative care and community nursing teams, provide most of the medical care for patients who die in the community at end of life. [10][11][12][13] Previous research suggests that GPs highly value this part of their work. 10,14 Patients benefit if the GP is accessible, provides continuity of care, takes time to listen, and addresses symptom-control concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In Belgium, almost 95% of the population have an FP whom they consult regularly (78% at least once a year). 33 FPs are considered to have a pivotal role in providing out-of-hospital end-of-life care 34 and are expected to be well informed about the patient's medical and social situation. Consequently, their perspectives are considered crucial when examining circumstances related to the hospital admission.…”
Section: Designmentioning
confidence: 99%